2010
DOI: 10.1016/j.quascirev.2009.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Highly skewed sex ratios and biased fossil deposition of moa: ancient DNA provides new insight on New Zealand's extinct megafauna

Abstract: the other three moa taxa combined at BHV. A subsample of 227 individuals had sufficient nuclear 28 DNA preservation to warrant the use of molecular sexing techniques, and the analyses uncovered a 29 remarkable excess of females in both deposits with an overall male to female ratio of 1 : 5.1. Among 30 juveniles of E. curtus, the only species which was represented by a substantial fraction of juveniles, 31 the sex ratio was not skewed (10 ♂, 10 ♀), suggesting that the observed imbalance arose as a result of 32 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
61
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(67 citation statements)
references
References 55 publications
6
61
0
Order By: Relevance
“…If adult female moa from each cohort were particularly attracted to the habitat around Pyramid Valley, whether foraging in groups of females or alone, it could explain the nonrandom relatedness distribution in our sample. It has previously been suggested that moa females maintained home ranges around the lakes, whereas males may have been more mobile (Allentoft et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…If adult female moa from each cohort were particularly attracted to the habitat around Pyramid Valley, whether foraging in groups of females or alone, it could explain the nonrandom relatedness distribution in our sample. It has previously been suggested that moa females maintained home ranges around the lakes, whereas males may have been more mobile (Allentoft et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Although 60% of the samples were from females from Pyramid Valley, the naive probability of all four related dyads belonging to this class of individuals is only 1.5%. Also, Allentoft et al (2010) showed a significant difference in the distribution of sexes and juveniles from the proximate fossil sites at Pyramid Valley and Bell Hill Vineyard (Figure 1). At Pyramid Valley, only two of 49 D. robustus individuals sampled were identified genetically as males and this extreme skew is likely a combination of higher mortality among males combined with behavioural differences or differential habitat preferences between the sexes (Allentoft et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations